Designing Oil Revenue Management Mechanisms : An Application to Chad - Campagne, Benoit; Kitzmuller, Markus; Tordo, Silvana (World Bank, Washington, DC, 2020)
Oil resources usually play a significant role in oil-rich countries, in gross domestic product and government revenues. High dependence of government revenues on oil can contribute to severe recession following an adverse commodity price shock, such as in 2014. This paper examines the extent to which a fiscal rule or stabilization fund could translate into a less pro-cyclical fiscal policy, with the government saving part of its oil revenues during periods of high prices and drawing down on the savings during difficult periods. Using the macro-structural model MFMod, the paper presents, evaluates, and discusses the strengths and weaknesses of different oil revenue management mechanisms applied to the specific case of Chad. The scenarios demonstrate that a well-designed management rule can successfully insulate the public budget from the oil price cycle, resulting in a significant reduction in the volatility of the economy.